2020
DOI: 10.1177/1038416220947085
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in obtaining employment in China: Lived experiences of Australian Chinese graduates

Abstract: Previous scholarly work has elaborated on challenges faced by Chinese international returnees at Chinese workplaces. However, limited research has captured to what extent such challenges have involved Chinese Australian graduates in gaining employment in China. Hence this study investigates the challenges involved in obtaining successful employment in China. Drawing on a qualitative study, semi-structured interviews were conducted with 19 Chinese graduates who studied at one Australian university and returned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…The employment trajectory of international education graduates is influenced by a range of economic, social and cultural factors (Amazan et al, 2016;Hao & Welch, 2012;Hao et al, 2016;Nachatar Singh, 2020). Economic factors such as limited jobs (Abimbola et al, 2016;Amazan et al, 2016), saturated fields caused by an overly competitive domestic labour market (Abimbola et al, 2016;Amazan et al, 2016;Hao & Welch, 2012;Nachatar Singh, 2020) and high salary expectations against those offered in the market (Hao & Welch, 2012;Hao et al, 2016;Perna et al, 2015) make it challenging for the graduates to obtain post-graduation employment.…”
Section: Fac Tor S Influen Cing International Educ Ation G R Aduate S' Employmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The employment trajectory of international education graduates is influenced by a range of economic, social and cultural factors (Amazan et al, 2016;Hao & Welch, 2012;Hao et al, 2016;Nachatar Singh, 2020). Economic factors such as limited jobs (Abimbola et al, 2016;Amazan et al, 2016), saturated fields caused by an overly competitive domestic labour market (Abimbola et al, 2016;Amazan et al, 2016;Hao & Welch, 2012;Nachatar Singh, 2020) and high salary expectations against those offered in the market (Hao & Welch, 2012;Hao et al, 2016;Perna et al, 2015) make it challenging for the graduates to obtain post-graduation employment.…”
Section: Fac Tor S Influen Cing International Educ Ation G R Aduate S' Employmentmentioning
confidence: 99%
“…Sociocultural factors also have a significant impact, and local cultural expectations place tremendous pressure on international education graduates. Research on Chinese graduates showed that families expected them to smoothly transition from university life to a workplace (Gill, 2010), whereas employers expected them to be considerably superior to their local counterparts (Hao & Welch, 2012) making reintegration into the domestic cultural environment difficult (Gill, 2010;Hao & Welch, 2012;Hao et al, 2016;Nachatar Singh, 2020;Pham et al, 2019).…”
Section: Fac Tor S Influen Cing International Educ Ation G R Aduate S' Employmentmentioning
confidence: 99%
See 3 more Smart Citations